2020
DOI: 10.48550/arxiv.2009.07154
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Open-loop Deterministic Density Control of Marked Jump Diffusions

Kaivlaya Bakshi,
Evangelos A. Theodorou

Abstract: The standard practice in modeling dynamics and optimal control of a large population, ensemble, multi-agent system represented by it's continuum density, is to model individual decision making using local feedback information. In comparison to a closed-loop optimal control scheme, an open-loop strategy, in which a centralized controller broadcasts identical control signals to the ensemble of agents, mitigates the computational and infrastructure requirements for such systems. This work considers the open-loop,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…We have shown that optimal control theory is a natural and powerful framework for the design and study of thermodynamically optimal protocols. In the spirit of [61], it is our hope that through considering the optimal control of non-equilibrium probability densities considered here and elsewhere [34,36,33], we may better understand how it is that biological systems, which operate far from equilibrium, function efficiently across vastly different length-and time-scales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that optimal control theory is a natural and powerful framework for the design and study of thermodynamically optimal protocols. In the spirit of [61], it is our hope that through considering the optimal control of non-equilibrium probability densities considered here and elsewhere [34,36,33], we may better understand how it is that biological systems, which operate far from equilibrium, function efficiently across vastly different length-and time-scales.…”
Section: Discussionmentioning
confidence: 99%
“…We may then apply Pontryagin's maximum principle, one of OCT's foundational theorems, to yield Hamiltonian partial differential equations whose solutions directly give optimal protocols. We note that the optimal control of fields and stochastic systems has been previously studied within applied mathematics and engineering literature [33,34,35,36,37,38,39,40,41,42], but to our knowledge it has never been used to derive exact optimal work-minimizing protocols in stochastic thermodynamics.…”
Section: Introductionmentioning
confidence: 99%